Emotional Spiritual Quotient (Esq) Guidance In Improving Prophetic Motivation (Study on Motivators biMBA AIUEO Ciparay Bandung) - Gina Rismawati; Dindin Solahudin; Sugandi Miharja (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This research is motivated by the importance of the role of Emotional Spiritual Quotient (ESQ) guidance in building prophetic motivation for motivators at biMBA AIUEO Ciparay. Prophetic motivation which includes the values ??of faith, being a learner, and doing good becomes an essential moral-spiritual foundation in carrying out the mission of mentoring, namely guiding children's learning interests in a fun, individual, and compassionate manner. However, before ESQ guidance was implemented, some motivators still viewed this task as merely routine work or achieving academic targets. This research aims to: (1) Describe the concept of ESQ guidance in increasing prophetic motivation of motivators at biMBA AIUEO Ciparay; (2) Analyze the implementation of ESQ guidance in building prophetic motivation of motivators; and (3) Identify the impact of ESQ guidance on prophetic motivation of motivators. The research results show that ESQ guidance at biMBA AIUEO Ciparay is structured through biMBA Joint Learning (BBb) activities, Volunteer Refresher Training (TPR), and Rohis Study which are carried out regularly. Its implementation focuses on internalizing the values ??of faith, becoming a learner, and doing good through a fun and responsible mentoring process. The impact is seen in increasing the spiritual awareness of motivators, the ability to manage emotions, a paradigm shift in the main purpose of life, and a reinterpretation of the mentoring process as worship and a field of charity.